This preview shows page 1. Sign up to view the full content.
Unformatted text preview: result = ((z*(xy) + x^(z+y)) / (y/z  x^(2+y)*(5*z2*y)))^(x*y*z) 3. Create the variable y given by the set of data { 1 ,2 , . 5 , 5 ,3 } . Then calculate z = 2 ( y + 3) y + ye y for all values of y . >> y = [1,2,0.5,5,3]; >> z = 2*(y+3).^y + y.*exp(y)...
View
Full
Document
This note was uploaded on 02/14/2010 for the course ASE 201 taught by Professor Hayes during the Spring '07 term at University of Texas at Austin.
 Spring '07
 Hayes

Click to edit the document details